The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0004-282x2001000600018
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy for acute extra-cranial artery dissection: report of two cases

Abstract: -Extra-cranial arterial dissection accounts for 10% of strokes in young people. Information on safety of thrombolytic administration in this group is limited. The literature, however, does not favor use of thrombolytics for myocardial ischemia when peripheral arterial dissection coexists. Based on the clinical and radiological features, two patients who presented with acute stroke secondary to arterial dissection were considered for thrombolysis. One of them received intra-venous recombinant tissue plasminogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
7
0
2
Order By: Relevance
“…In spite of providing insufficient data for assessment of efficacy, four non-randomised studies of intravenous thrombolysis showed that complication rates were no greater than thrombolysis for other ischemic stroke etiologies, suggesting that this treatment should not be withheld in patients with suspected SCAD [48][49][50][51] . regarding intra-arterial thrombolysis (IAT), few case reports have been published and showed no rupture of the dissected vessel, intracranial or subarachnoid hemorrhage or peri-interventional arterial embolism 52,53 . Surgery or endovascular procedures have been described in patients with persistent or progressive symptoms despite adequate clinical therapy, in those with hemodynamically significant residual stenosis, or in the presence of contraindications to anticoagulant therapy 31,54 .…”
Section: Treatmentmentioning
confidence: 99%
“…In spite of providing insufficient data for assessment of efficacy, four non-randomised studies of intravenous thrombolysis showed that complication rates were no greater than thrombolysis for other ischemic stroke etiologies, suggesting that this treatment should not be withheld in patients with suspected SCAD [48][49][50][51] . regarding intra-arterial thrombolysis (IAT), few case reports have been published and showed no rupture of the dissected vessel, intracranial or subarachnoid hemorrhage or peri-interventional arterial embolism 52,53 . Surgery or endovascular procedures have been described in patients with persistent or progressive symptoms despite adequate clinical therapy, in those with hemodynamically significant residual stenosis, or in the presence of contraindications to anticoagulant therapy 31,54 .…”
Section: Treatmentmentioning
confidence: 99%
“…In 6 patients with sICAD who underwent IAT, no rupture of the dissected vessel, cervical, subarachnoid or intracranial hemorrhage, or periinterventional (Furlan et al 1999) arterial embolism was described (Abboud et al 2005;Arnold et al 2002;Sampognaro et al 1999;Zaidat et al 2001). Nedeltchev et al (Nedeltchev et al 2005) reported a patient with sICAD causing symptomatic occlusion of the middle cerebral artery who underwent MT without adverse events.…”
Section: Intraarterial and Mechanical Thrombolysismentioning
confidence: 99%
“…Small case series and case reports have documented the successful treatment of ischemic stroke associated with cervicocranial artery dissection with intravenous and intra-arterial thrombolysis [77][78][79][80][81]. Others advocate the use of endovascular or surgical therapy for stroke prevention in selected patients with persistent severe stenosis or occlusion after internal carotid artery dissection and recurrent cerebral ischemic symptoms despite medical therapy.…”
Section: Treatment and Prognosismentioning
confidence: 99%